Path coefficient analysis of seed yield in Indian mustard [Brassica juncea (L.) Czern. and Coss.] under drought: PATH COEFFICIENT ANALYSIS OF SEED YIELD IN INDIAN MUSTARD UNDER DROUGHT - R L MEENA,; J S CHAUHAN,; K H SINGH,; S S RATHORE, (Journal of Oilseeds Research, 2015)
The present investigation was carried out to assessthe components ofseed yield under droughtstress using path coefficient analysis. Twenty two genotypes ofIndian mustard were grown in a Randomized Complete Block Design with three replications during rabi, 2007-08. Analysis of variance indicated presence of variability in the experimental genotypesforseed yield and other morpho-physiological characters except main shoot length, harvest index, protein content, SLW at 35 days aftersowing (DAS) and seed: husk ratio. Seed yield/plant was positively and significantly correlated at both phenotypic and genotypic levels with days to maturity, plant height, primary branches/plant, secondary branches/plant, siliquae on main shoot, LAI, CGR and biological yield/plant. Seed yield/plant had negative genotypic correlations of moderate strength with transpiration quotient at 35 and 75 DAS indicating its positive relationship with water use efficiency. TheRGRduring 35-75 DAS followed byRGRbetween 75 and 95 DAS exerted the highest direct positive effects on seed yield. Biological yield/plant, SLW at 75 DAS, TDM at 75 and 95 DAS, SCMR at 35 DAS, siliquae on main shoot, days to maturity and siliqua length also had substantial positive direct effects. The characters under study explained about 96.5% and 100% variability in the seed yield at phenotypic and genotypic level, respectively. Dry matter production, early growth and development of the crop are important under drought due to continuous decline in available soil moisture. Since LAI, LGR, CGR, RGR and NAR are the functions of dry matter production and/or leaf area, therefore, selection on the basis of high biological yield and large LAI at 50% flowering should be quite effective in improving seed yield under drought. An increase in LAI might increase radiation load resulting in to high transpiration. Therefore, genotypes having high LAI with erect leaves and low TQ should be accorded priority in the selection programme.